1989
DOI: 10.1073/pnas.86.1.133
|View full text |Cite
|
Sign up to set email alerts
|

Site-directed mutagenesis of the catalytic residues Asp-52 and Glu-35 of chicken egg white lysozyme.

Abstract: The roles of the catalytic active-site residues aspartic acid-52 and glutamic acid-35 of chicken lysozyme (EC 3.2.1.17) have been investigated by separate in vitro mutagenesis of each residue to its corresponding amide (denoted as D52N and E35Q, respectively). The mutant enzyme D52N exhibits =5% of the wild-type lytic activity against Micrococcus luteus cell walls, while there is no measurable activity associated with E35Q (0.1% ± 0.1%). The measured dissociation constants for the chitotriose-enzyme complexes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
129
1

Year Published

1993
1993
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 172 publications
(136 citation statements)
references
References 45 publications
6
129
1
Order By: Relevance
“…Site-directed mutagenesis of the hen egg-white lysozyme gene was performed according to Malcolm et al (1989) with modifications described by Shih et al (1993) and Matsumura and Kirsch (1996). Expression and purification were carried out according to KamMorgan et al (1993) and Matsumura and Kirsch (1996).…”
Section: Expression Of Mutant Lysozymesmentioning
confidence: 99%
“…Site-directed mutagenesis of the hen egg-white lysozyme gene was performed according to Malcolm et al (1989) with modifications described by Shih et al (1993) and Matsumura and Kirsch (1996). Expression and purification were carried out according to KamMorgan et al (1993) and Matsumura and Kirsch (1996).…”
Section: Expression Of Mutant Lysozymesmentioning
confidence: 99%
“…It was putative active site, the titration of at least one of them with demonstrated that substitutions of this residue for homoserine silver or mercury ions leads to a complete loss of the Upase by selective chemical modification [21] or for asparagine by activity. It was shown that Cys 136 may be selectively modified site-directed mutagenesis [22] led to significant enzyme inactiwith 2,4,6-trinitrobenzene sulfonate, the modification being acvation (90-95%) without sufficient changes in the substrate companied by enzyme inactivation. Phosphate addition would affinity.…”
Section: ~ 310mentioning
confidence: 99%
“…Biochemical investigation of the HEWL.Fab-IO system are facilitated by the heterologous expression of HEWL (Malcolm et al, 1989). The antibody partially occludes the HEWL active site causing the HEWL.Fab-10 complex to be nearly devoid of lysozyme activity.…”
mentioning
confidence: 99%